Challenges and Benefits of Approaches Used to Integrate Regional Monitoring Programs - Arciszewski, T. J.; Roberts, D. R.; Munkittrick, K. R.; Scrimgeour, G. J. (Frontiers in Environmental Science, 2021)
Understanding the extent of human influence on the environment and informing regulation and management is a role of ecological monitoring. Although challenging to develop and operate, some degree of integrated monitoring is often necessary, especially at regional scales, to address the complex questions of environmental management and regulation. The concept of integration is well-understood, but its practice across programs and studies can be diverse motivating a deeper examination of the exiting general approaches. We suggest integrated monitoring occurs in three ways: interpretation, analysis, and design. Design can be further subdivided into partial and full integration. In this work we define these types of integration and describe their benefits and challenges using the Oil Sands Monitoring program in northern Alberta as a practical example. From this examination and our experiences, we suggest a one-size-fits-all integrated design is not likely possible within a multi-media regional monitoring program. We further suggest a fully integrated design may always be unachievable and ultimately undesirable, except where scope is limited, monitoring questions are clearly understood, and approaches are widely accepted. Instead, a successful program will include a mixture of the three types of integration among studies depending on the desired and acceptable attributes, including flexibility to address new questions and strength of inference.